Legal Pluralism and Analytical Jurisprudence: An Inapposite Contrast - Fabra-Zamora, Jorge (McGill Law Journal / Revue de droit de McGill, 2021)
The intellectual tradition of legal pluralism characterizes itself by way of a contrast to legal centralism or monism. Self-styled pluralists typically attribute centralist and monist views to mainstream theories of law, which I call here analytical jurisprudence. This article argues that the pluralist foundational contrast with analytical jurisprudence suffers from three recurrent defects. First, the pluralist opposition to analytical jurisprudence conflates conceptual questions with empirical, doctrinal, and politico-moral inquiries. Second, pluralists misattribute to analytical jurisprudents an equation between law and state that they do not hold and have the resources to reject. Third, pluralists address the conceptual problems of legal theory by relying on definitions and other reductive methodologies long rejected by analytical jurisprudents. My central claim is that this trio of recurrent defects, which has also been incorporated into the reconciliatory project termed “pluralist jurisprudence,” should be laid to rest.